Genetic Etiology Shared by Multiple Sclerosis and Ischemic Stroke - Tian, Zhu; Song, Yang; Yao, Yang; Guo, Jie; Gong, Zhongying; Wang, Zhiyun (Frontiers in Genetics, 2020)
Although dramatic progress has been achieved in the understanding and treatment of multiple sclerosis (MS) and ischemic stroke (IS), more precise and instructive support is required for further research. Recent large-scale genome-wide association studies (GWAS) have already revealed risk variants for IS and MS, but the common genetic etiology between MS and IS remains an unresolved issue. This research was designed to overlapping genes between MS and IS and unmask their transcriptional features. We designed a three-section analysis process .In section 1, we computed gene-based analyses of MS-GWAS and IS-GWAS datasets by VGEAS2. In section 2, overlapping genes of significance were identified in a meta-analysis using the Fisher procedure. In section 3, we performed gene expression analyses to confirm transcriptional changes. We identified 24 shared genes with Bonferroni correction (Pcombined<2.31E-04), and 5 (FOXP1, CAMK2G, CLEC2D, LBH, and SLC2A4RG) had significant expression differences in MS and IS Gene Expression Omnibus (GEO) datasets. These meaningful shared genes between IS and MS shed light on the underlying genetic etiologies shared by the diseases. Our results provide a basis for in-depth genomic studies of associations between MS and IS.